Spontaneous Regression of Congenital Cholesteatoma: A Report of Two Cases with Differing Ossicle Involvement (Archives of Clinical and Medical Case Reports, 2019)
The mechanism of congenital cholesteatoma has not been clarified yet. Usually, middle ear cholesteatoma (congenital and acquired) is a progressive and destructive disease that requires surgery for complete cure. In recent years, early detection of congenital cholesteatomas has become more frequent due to advances in endoscopy and microscopy. Along with these developments, there have been reports of congenital cholesteatoma regressing spontaneously, as seen by tympanic and computed tomography findings over time. Herein, we report two cases of spontaneous regression of cholesteatoma, both with ossicular chain malformation. One cholesteatoma was close to the ossicles. In the other case, the cholesteatoma and ossicle were separated; however, the ossicular morphology was inconsistent with that of congenital ossicular malformation. Further similarities and differences between these two cases are discussed herein.